Deficiency of Iron: A Risk Factor in Pregnant Women in the District Swat - Naseer Ullah; Irum Hassan; Maria Rahman; Akhtar Rasool; Ikram Ilahi; Muhammad Attaullah; Sayed Ihtishamullah; Muhammad Israr (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Iron is an essential element for the body. Its requirements increase during pregnancy. Improper use of iron may lead to anaemia in the mother. Anaemia may lead to complications such as abortion, stillbirth, and congenital abnormalities in the fetus of pregnant women. This study aimed to determine the iron level and problems associated with iron deficiency in pregnant women in Swat District. Samples were collected from eight hundred pregnant women. The iron status was determined by measuring haemoglobin levels using Sahli’s Method and the Haematology Analyzer. In total, 54 % were anaemic. The age group 41-45 was highly anaemic (100 %) followed by 15-20 (74 %) while the 31-35 age group was the least anaemic (42 %). The Underweight was the highly anaemic group (83 %) and the obese were the least anaemic group (12 %). Pregnant women with second trimester gestational age were the least anaemic (34 %) while the third trimester was the highly anaemic (67 %). It was concluded that iron deficiency is a common issue in pregnant women in District Swat.